Mapping of quantitative trait locus reveals PsXI gene encoding xylanase inhibitor as the candidate gene for bruchid (Callosobruchus spp.) resistance in pea (Pisum sativum L.) - Yan, Jianjun; Chen, Jingbin; Lin, Yun; Yuan, Xingxing; Somta, Prakit; Zhang, Yaowen; Zhang, Zeyan; Zhang, Xianhong; Chen, Xin (Frontiers in Plant Science, 2023)
Pea (Pisum sativum L.) is an important legume crop for both food and feed. Bruchids (Callosobruchus spp.) are destructive insect pests of pea in the field and during storage. In this study, we identified a major quantitative trait locus (QTL) controlling seed resistance to C. chinensis (L.) and C. maculatus (Fab.) in field pea using F2 populations derived from a cross between PWY19 (resistant) and PHM22 (susceptible). QTL analysis in the two F2 populations grown in different environments consistently identified a single major QTL, qPsBr2.1, controlling the resistance to both bruchid species. qPsBr2.1 was mapped onto linkage group 2 between DNA markers 18339 and PSSR202109 and explained 50.91% to 70.94% of the variation in resistance, depending on the environment and bruchid species. Fine mapping narrowed down qPsBr2.1 to a genomic region of 1.07 Mb on chromosome 2 (chr2LG1). Seven annotated genes were found in this region, including Psat2g026280 (designated as PsXI), which encodes a xylanase inhibitor and was considered as a candidate gene for bruchid resistance. PCR amplification and sequence analysis of PsXI suggested the presence of an insertion of unknown length in an intron of PWY19, which causes variation in the open reading frame (ORF) of PsXI. Moreover, the subcellular localization of PsXI differed between PWY19 and PHM22. These results together suggested that PsXI encoding xylanase inhibitor is responsible for the bruchid resistance of the field pea PWY19.